Morphological Errors Analysis on Students’ Synopsis Writing - Irpan Ali Rahman (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
The objective of the study is to find out the students’ morphological errors in synopsis writing. It aimed to know what the difficulty is faced by the students in their synopsis writing. The methodology of study is a qualitative that focused to analyze the students’ synopsis writing errors. The research finding is found that several students have synopsis writing errors in some aspects refer to omission, misordering, misinformation, and addition.